Analisis Filosofis Lambang Institut Agama Islam Negeri (IAIN) Pontianak - Fitriyanto, Andry; Septian Utut (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This paper is part and development of the research results entitled Historical Map of Pontianak IAIN Policy Directions. Contains a discussion of the symbol of IAIN Pontianak as a symbol of institutional identity. The symbol is termed as a sign which is a medium of communication between the owner and the public. Some messages are conveyed and captured by everyone who sees it. This study uses Charles Sanders Peirce's semiotic analysis method with a triangle meaning. Includes ground (sign), denotatum (object), and interpretant. These three aspects are used to see the elements of the symbols contained in the IAIN Pontianak symbol. Also to see how the work and the relationship between these elements present a certain meaning to the public. The results of this study are; First, the IAIN Pontianak symbol consists of a combination of picture marks and letter marks. picture mark consisting of a flower symbol with six outers and five inner petals, an equator monument, a carved fern motif typical of West Kalimantan, a nib, open book/book. While the letter mark is the words "Iain Pontianak" on the symbol. Second, these elements reflect the spirit of scholarship, moderate Islam, and Borneo culture. The scientific spirit is represented by the symbol of a pen tip and an open book. Meanwhile, the moderate Islamic spirit is represented by an open book/book which is translated as the Qur'an, the six outer petals and five inner petals of the flower depict the six pillars of faith and the pillars of Islam, the symbol of the equator monument reflects a moderate Islamic style. The spirit of Borneo culture can be seen from the symbol of the equator monument which is the brandmark of the capital of West Kalimantan, the fern motif which comes from the Dayak tribe, and the green and yellow colors which are the colors of greatness for the Malay people who are also widely spread on the island of Borneo. Third, the symbol has a strong relevance to the vision of IAIN Pontianak (Excellent and open in scientific, Islamic, and cultural studies and research of Borneo). Fourth, several aspects of the symbol can be reinterpreted. This is to strengthen the positive image displayed. Among them are "five petals in a flower" which can be identified with Pancasila to produce nationalism values. then the flower symbol consists of a series whose individual parts are not connected. can be interpreted as an acknowledgment of diversity which is united by the spirit of togetherness within a larger frame. Key Words: Semiotic; symbol; IAIN Pontianak.